The new economy of oil impacts on business, geopolitics, and society - Mitchell, John V. (Royal Institute of International Affairs, Energy and Environment Programme Earthscan, 2001)
In a world where international accountability is increasingly important, the oil industry faces an unprecedented series of challenges. This book states that the acceptability of oil is becoming more important than its availability. It is suitable for those involved with oil - from industry professionals to competitors, investors, and regulators.